2020
DOI: 10.1186/s12935-020-01343-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a molecular prognostic index of bladder cancer based on immunogenomic landscape analysis

Abstract: Background: Bladder cancer (BCa) is one of the important tumors that have been proven to be treatable with immunotherapy. This study aims to identify and validate a molecular prognostic index of BCa based on immunogenomic landscape analysis. Methods: The cancer genome atlas (TCGA) database and immunology database and analysis portal (ImmPort) database were used to identified differentially expressed immune-related genes (IRGs). Prognostic IRGs were screened and protein-protein interaction (PPI) network was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…There were various components in the tumor microenvironment including tumor cells, immune cells, stromal cells, and extracellular matrix [22]. The ESTIMATE algorithm, which was developed by Yoshihara et al, was recently widely used for exploring tumor microenvironment components [22][23][24]. We calculated stromal score, immune score, ESTI-MATE score, and tumor purity of COAD tumor microenvironment using the ESTIMATE algorithm.…”
Section: Relationships Between Stemness Indices and Tumormentioning
confidence: 99%
“…There were various components in the tumor microenvironment including tumor cells, immune cells, stromal cells, and extracellular matrix [22]. The ESTIMATE algorithm, which was developed by Yoshihara et al, was recently widely used for exploring tumor microenvironment components [22][23][24]. We calculated stromal score, immune score, ESTI-MATE score, and tumor purity of COAD tumor microenvironment using the ESTIMATE algorithm.…”
Section: Relationships Between Stemness Indices and Tumormentioning
confidence: 99%
“…A recent study 13 has constructed a ceRNA network, which was of high prognostic value, to achieve a deeper comprehension to the RNA regulatory network in BLCA. Besides, although several immune-relevant signature [34][35][36] have been constructed to predict the survival of BLCA, few studies concentrated on immune-relevant genes revealing the prognosis based on ceRNA hypothesis. In this study, we integrated the TCGA-BLCA database and GEO database to determine an immune-related risk signature and constructed an immune-relevant ceRNA network including 5 mRNAs, 24 miRNAs and 86 lncRNAs, leading to a better understanding of the oncological immunology of BLCA from the angle of RNA interactions.…”
Section: Discussionmentioning
confidence: 99%
“…By means of immune grouping and correlation test, we ensure the risk score is closely correlated with tumor immunity. Compared with other immune-related risk models [34][35][36] , we rstly made use of ceRNA hypothesis to establish a prognostic signature in order to make sure the risk score was immune-related. The analysis results of functional annotation indicated that the immune-related pathways, such as complement and in ammatory response, were signi cantly enriched in the high-risk group, which once again veri ed the immunological correlation of risk score.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome and clinical data of BCa were obtained from TCGA database (https://portal.gdc.cancer.gov), including 414 BCa cases and 19 normal cases [14]. The clinical features of BCa patients included age, gender, grade, T stage, N stage, M stage, and AJCC stage.…”
Section: Data Acquisitionmentioning
confidence: 99%